Efficiency of the Rome Statute of the International Criminal Court in prosecuting state officials for committing international crimes - Lapiņa, Laura (Riga Graduate School of Law, 2018)
The aim of the present thesis is to examine and assess the efficiency of the International Criminal Statute in prosecuting state officials for committing international crimes. More precisely the thesis will discuss the Rome Statute of International Criminal Law. The importance lays within the hope for the Rome Statute and the International Criminal Court to end the impunity of the State Officials and prosecute the international criminals in a fair trial. The debate of the effectiveness of the Statutes has been ongoing since the moment of the Rome Statute Treaty coming into force in 1998.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; International criminal law; Rome Statute